Hematopoietic stem cell transplantation in systemic sclerosis - K G Chengappa; V S Negi (Indian Journal of Rheumatology)
Systemic sclerosis (SSc) is a disease associated with a significant morbidity and mortality, with relatively small benefits seen with immunosuppression. Of late, hematopoietic stem cell transplantation has emerged as a promising therapy for SSc with a significant reduction in mortality in the longer term. We discuss the principles behind stem cell transplantation in SSc as well as the recent trials which have shown significant promise with this technique.